Analisis Wacana Kritis tentang Pronomina Persona dalam Pidato yang disampaikan oleh Greta Thunberg - Yuli Suryaningsih (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2021)
Although the study of personal pronouns in speeches is very popular, only a few studies are conducted to analyze non-political speeches. In spite of Greta Thunberg’s famous and bold speaking manners, none of the researchers are interested to look deeper at speeches delivered by the young activist. In this study, I employ Fairclough’s model of Critical Discourse Analysis to examine the use of 102 first-and-second person personal pronouns in her speeches. Forty-seven percent of the pronouns are you and twenty-five percent of the pronouns are we. Furthermore, the high percentage of the occurrence towards you and we shows the characterization of her speeches. It shows both othering strategy and personalization strategy between the speaker and the audience. In addition, the pronouns act both as inclusive and exclusive. The variation of inclusiveness and exclusiveness is highly affected by who the audience is. These findings propound that the use of the same pronouns by the same person acts differently depending on who the audience is.